Phosphorus and Weeding on Growth and Yield of Mungbean (Vigna radiata L.) - Asaduzzaman, M.; Chowdhury, S.; Ali, M. A. (International Journal of Bio-resource and Stress Management, 2010)
An experiment was conducted to study the influence of phosphorus and weed management on growth and yield performance of mungbean (Vigna radiata L.). Experiment consisted of four levels of phosphorus (P205), viz. P0 (0 kg P205), P1 (30 kg P205), P2 (60 kg P205), and P3 (90 kg P205)ha-1; and three levels of weeding (W), viz. W0 (no weeding), W1 (one weeding), and W2 (two weeding) with 12 treatment combinations (P0W0, P0W1, P0W2, P1W0, P1W1, P1W2, P2W0, P2W1, P0W2, P3W0, P3W1 andP3W2) and three replications. 60 kg P205 showed significantly highest values on all parameters studied. Response of different weeding levels was significant for all the parameters except test weight and total dry matter at early growth stage. Weeding twice performed best for all the parameters. Application of 60 kg P205 in combination with two weeding recorded the highest values in all parameters except number of seeds pod-1 which was highest in P205 at 60 kg ha-1. The study recommends that 60 kg P2O5 ha-1 along with two weeding produce best mungbean during summer season.